Soil liquefaction potential assessment using ambient noise: A case study in Pohang, Korea - Kang, Su Young; Kim, Kwang-Hee; Gihm, Yong Sik; Kim, Byungmin (Frontiers in Earth Science, 2022)
An MW 5.5 earthquake occurred in Pohang, Korea, on 15 November 2017 and caused large damage. In and around the epicentral area the earthquake also remained numerous sand boils, which is a surface representation of soil liquefaction at shallow depth during the earthquake. Soil liquefaction is one of the most dangerous consequences of an earthquake. Here we show that the spatial distribution of the ground vulnerability index (Kg), which we estimate via ambient noise analysis, correlates very well with the distribution of sand boils. Our Kg model based on the dense microtremor surveys at differing geological conditions and urbanizations indicates that only 28.4% of the study area is vulnerable to ground shaking (Kg > 20), with 91.1% of the observed sand boils occurring in these vulnerable areas. We also observed that Kg values estimated in the study correlate well with both VS30 values and geologic units in the study area. This case report confirmed that the Kg can be an affordable supplement to traditional, but expensive and time-consuming, geotechnical/geophysical techniques for the initial screening and regional evaluations. Such a Kg map can assist stakeholders in earthquake-prone regions in identifying areas more susceptible to liquefaction and bring a recommendation to consider seismic hazard mitigation.